2013
DOI: 10.1016/j.jare.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PIVKA-II in diagnosis of hepatocellular carcinoma

Abstract: Liver cancer grows silently with mild or no symptoms until advanced. In the absence of an effective treatment for advanced stage of hepatic cancer hope lies in early detection, and screening for high-risk population. Among Egyptians viral hepatitis is the most common risk factor for hepatocellular carcinoma (HCC). The current work was designed to determine the level of prothrombin induced by vitamin K absence-II (PIVKA-II) in sera of patients suffering from HCC and hepatitis C virus (HCV) patients being the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
(48 reference statements)
5
24
1
Order By: Relevance
“…In the present study there was a highly significant increase in serum creatinine activity in the HCC group compared to control and untreated HCV infected group P<0.001, P = 0.004 respectively, this result disagree with Nguyen et al [37] and Zakhary et al [38] who reported that the level of creatinine non significantly decrease in HCC group compared to other studied groups.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the present study there was a highly significant increase in serum creatinine activity in the HCC group compared to control and untreated HCV infected group P<0.001, P = 0.004 respectively, this result disagree with Nguyen et al [37] and Zakhary et al [38] who reported that the level of creatinine non significantly decrease in HCC group compared to other studied groups.…”
Section: Discussioncontrasting
confidence: 98%
“…In our study when using receiving operator characterizing curve (ROC curve) to reach the value of the best sensitivity and specificity for AFP, it was found that at a value of 3.39 ng/ml (the best cut off) yields, the sensitivity was 52% and the specificity was 40%. Zakhary et al [38] reported a cutoff of as a diagnostic cutoff. According to our results, at a cut-off 28 ng/dl shows the sensitivity was (73.3%) and specificity was (75%).…”
Section: Discussionmentioning
confidence: 99%
“…So, they concluded that GPC-3 is a sensitive serum and tissue marker for the diagnosis of early HCC. Several studies have shown that Glypican-3 is superior to AFP in early detection of HCC, being highly sensitive and specific (Suriawinata et al, 2010;Zakhary et al, 2012). Studies performing double combination of Glypican-3 and AFP found sensitivities between (84%-92%) and specificities between (90%-95%).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, some authors, and especially Japanese guidelines on HCC management proposed the use of PIVKA-II for routine follow-up in patients with high risk for developing HCC (5,20), as well as a prognostic biomarker before surgery to predict microvascular invasion, relapse and overall poor prognosis (14)(15)(16)(17). In detail, Japanese guidelines have suggested to consider as a diagnostic marker of HCC high elevation of tumor markers, namely AFP ≥200 ng/ml and PIVKA-II ≥40 mAU/ml.…”
mentioning
confidence: 99%